Kedudukan Lagu Indonesia Raya dalam Sistem Ketatanegaraan Indonesia Sebagai Upaya Mencegah Krisis Multidimensi Nasional - Harmoko, Pungki; Taufik , Taufik (Riviera Publishing, 2025)
This study examines the position of the three-stanza song Indonesia Raya in the Indonesian state system to shape a culture of legal awareness and national spirit. The second and third stanzas contain messages of noble values of legal awareness and behavior as well as maintaining the sanctity of the homeland. However, in its implementation, only one stanza is commonly sung, even though the three stanzas of Indonesia Raya have been regulated in Law Number 24 of 2009 concerning the Flag, Language, and National Emblem as well as the National Anthem. Therefore, revitalization efforts are needed so that the song Indonesia Raya can function fully as a means of revolutionizing the mentality and character of the nation, towards a golden Indonesia in 2045.